Expeditious and eco-friendly fabrication of highly uniform microflower superstructures and their applications in highly durable methanol oxidation and high-performance supercapacitors. Issue 31 (21st July 2016) - Radhakrishnan, Sivaprakasam; Kim, Hak-Yong; Kim, Byoung-Suhk
Abstract : It is important to exploit copper sulfide products with desired structures as well as their potential applications owing to their simple synthesis, low cost and low toxicity. Abstract : It is important to exploit copper sulfide products with desired structures as well as their potential applications due to their simple synthesis, low-cost and low toxicity. In this work, a novel 3D copper sulfide (CuS) microflower (MF) superstructure was fabricated on a large scale through a facile, environment-friendly and inexpensive synthesis method. The as-prepared CuS superstructures with a diameter of about 4.0 ± 0.5 μm are assembled from large amounts of interleaving nanosheets, which have a uniform thickness of about 15 ± 3 nm. The effect of reaction time, temperature, solvents and different copper and sulfur sources on the formation of the 3D CuS MF superstructure was investigated. Furthermore, the formation mechanism was studied based on XRD and FESEM observations by time and temperature dependent experiments during the formation of the MF structures. Furthermore, the electrochemical supercapacitance and methanol oxidation properties of the 3D CuS MF superstructures were also investigated. The CuS MF superstructures have demonstrated enhanced capacitance, with a maximum specific capacity of 438 F g −1 at 3 mA cm −2, and good cycling stability, retaining about ∼87% of their capacitance after 2000 charge–discharge cycles as well as improved supercapacitor energy density without drop in power density. As a catalyst for methanol electro-oxidation, the CuS MF superstructures showed high current density (7.7 mA cm −2 ), high catalytic rate constant (1.01 × 10 6 cm 3 mol −1 s −1 ) and good long-term stability.